An annotated checklist of the earthworm fauna of Turkey (Oligochaeta: Lumbricidae) - Csuzdi, Cs.; Zicsi, A.; Misirlioòlu, M. (Zootaxa, 2006)
A checklist of the Lumbricid earthworms in Turkey is presented. Each entry is accompanied by complete references and, where it is appropriate, remarks are also added. The present list consists of 66 species of which 24 spp. (36.4%) seem to be Anatolian endemics. This indicates a highly specialized earthworm fauna predominated by the representatives of the genera Healyella Omodeo & Rota, 1989 and Dendrobaena Eisen, 1874.